Improved clinical outcomes of preimplantation genetic testing for aneuploidy using MALBAC-NGS compared with MDA-SNP array - Wenbin Niu; Linlin Wang; Jiawei Xu; Ying Li; Hao Shi; Gang Li; Haixia Jin; Wenyan Song; Fang Wang; Yingpu Sun (BMC, 2020)
Abstract Background To assess whether preimplantation genetic testing for aneuploidy with next generation sequencing (NGS) outweighs single nucleotide polymorphism (SNP) array in improving clinical outcomes. Methods A retrospective analysis of the clinical outcomes of patients who underwent PGT-A treatment in a single center from January 2013 to December 2017.A total of 1418 couples who underwent PGT-A treatment were enrolled, of which 805 couples used NGS for PGT-A, while the remaining 613 couples used SNP array for PGT-A. Clinical pregnancy rate, miscarriage rate and healthy baby rate were compared between the MALBAC-NGS-PGT-A and MDA-SNP-PGT-A groups. Results After testing karyotypes of 5771 biopsied blastocysts, 32.2% (1861/5771) were identified as chromosomally normal, while 67.8% were chromosomally abnormal. In terms of clinical outcomes, women in the MALBAC-NGS-PGT-A group had a significantly higher clinical pregnancy rate (50.5% vs 41.7%, p = 0.002) and healthy baby rate (39.6% vs 31.4%, p = 0.003), and a lower miscarriage rate (15.5% vs 22.8%, p = 0.036). Conclusion This is the largest study reporting the extensive application of NGS-based PGT-A, whilst comparing the clinical outcomes of MALBAC-NGS-PGT-A and MDA-SNP-PGT-A. The results provide greater evidence supporting the wider use of NGS in PGT-A, not only for its lower cost but also for its improved clinical outcomes compared to SNP-based PGT-A.